2022
DOI: 10.30935/cedtech/11811
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Instructional Feedback Scale: Validity and Reliability Study

Abstract: This study aimed to develop the "Students' Perception of Instructional Feedback Scale" (SPIFS) determining a framework related to the perception of instructional feedback by students. The sequential exploratory mixed method was used in the study. The study was conducted during the instructional design course offered to sophomores in the Department of Computer Education and Instructional Technology at two different universities. Accordingly, firstly a scale consisting of 31 items with Likert-type responses was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…We also found that feedback was not a predictor of students' learning performance (hypothesis H5). In that regard, our results contradict previous research that confirms the positive effect of feedback on students' learning performance (Baydas et al, 2022) even in formative assessment activities in EFL (Hwang & Chang, 2011;Nikou & Economides, 2018;Patra et al, 2022) and practice tests (Sepp et al, 2022). Our result might be explained by the type of feedback that was provided in the K-English application in this study: corrective feedback.…”
Section: Predictive Relevance Of the Structural Modelcontrasting
confidence: 99%
“…We also found that feedback was not a predictor of students' learning performance (hypothesis H5). In that regard, our results contradict previous research that confirms the positive effect of feedback on students' learning performance (Baydas et al, 2022) even in formative assessment activities in EFL (Hwang & Chang, 2011;Nikou & Economides, 2018;Patra et al, 2022) and practice tests (Sepp et al, 2022). Our result might be explained by the type of feedback that was provided in the K-English application in this study: corrective feedback.…”
Section: Predictive Relevance Of the Structural Modelcontrasting
confidence: 99%